Intracanal dressing and root canal filling materials in tooth replantation: a literature review - Barioni, Sônia Regina Panzarini [UNESP]; Trevisan, Carolina Lunardelli [UNESP]; Brandini, Daniela Atili [UNESP]; Poi, Wilson Roberto [UNESP]; Sonoda, Celso Koogi [UNESP]; Luvizuto, Eloa Rodrigues [UNESP]; Vendrame dos Santos, Claudia Leticia [UNESP] (Wiley-Blackwell, 2012)
The prognosis of tooth replantation is usually related to the need of endodontic treatment, which has a direct relationship with the occurrence of root resorptions. Several studies have been undertaken in an attempt to prevent, delay, or treat these complications, which are the main causes of loss of replanted teeth. This literature review examines research evidence on intracanal dressings and root canal filling materials used in cases of tooth replantation. A comprehensive search was performed in the Medline/Pubmed, Bireme and Scielo full-text electronic journal databases to retrieve English-language articles referring to these topics that had been published between 1964 and 2010. Calcium hydroxide (CH) remains the usually recommended choice as an intracanal medicament in replanted teeth; however, there is evidence to support the initial use of a corticosteroid-antibiotic combination such as Ledermix paste to control potential early resorption, prior to the introduction of CH where the beneficial effect in the treatment of progressive root resorption has been well proven. Regarding root filling materials, CH-containing sealers are a good option because of their biological properties. Accurate diagnosis and adequate treatment plan may constitute very complex tasks, particularly in tooth avulsion because several variables are involved. In addition to the technical knowledge and clinical experience directed toward the quality of treatment, patient education may favorably influence the survival of replanted teeth.